Isocitrate dehydrogenase mutation and microenvironment in gliomas: Do immunotherapy approaches matter? - Platten, Michael (Current opinion in neurology, 2025)
Purpose of review  - Gliomas with mutations in the gene for isocitrate dehydrogenase (IDH) display a unique immune microenvironment that is distinct from IDH-wildtype gliomas. This unique immune microenvironment is shaped by 2-hydroxyglutarate (2-HG), an oncometabolite produced by mutant IDH. These features provide an opportunity to develop and test targeted immunotherapies for IDH-mutant gliomas. - Recent findings  - IDH-mutant gliomas are characterized by an immunosuppressive tumor immune microenvironment (TIME) that suppresses the infiltration and activation of tumor-specific T cells. This is owed both to direct effects of the oncometabolite 2-hydroxyglutarate on glioma-infiltrating T cells and myeloid cells and indirect effects on the chemotactic profile of tumor cells. These immunosuppressive effects are reversed by IDH inhibitors recently approved for the treatments of IDH-mutant gliomas. At the same time, clinical trials have demonstrated encouraging results for targeted immunotherapies using vaccines targeting the most frequent mutation IDH1R132H. - Summary  - The reversal of the immunosuppressive effects by IDH inhibitors has opened exciting avenues for combinatorial immunotherapies such as vaccines and immune checkpoint inhibitors.
Gesehen am 01.12.2025